Central Lymph Node Metastasis Is an Important Prognostic Factor in Patients with Papillary Thyroid Microcarcinoma - Lee, Jeonghun; Song, Yeongpeck; Soh, Euy Young (Journal of Korean medical science, 2014)
Papillary thyroid microcarcinoma (PTMC) has been increasing, without a consensus for the management of this condition. In the present study, we analyzed the clinicopathological features of patients with PTMC to examine the impact of initial therapy and establish appropriate treatment. A total of 2,018 patients with PTMC were enrolled at a single university hospital. Of them, 1,245 patients (61.8%) underwent total thyroidectomy, and 1,838 patients (91.3%) underwent central lymph node (LN) dissection. Five-and 10-yr recurrence rates were 3.2% and 4.6%, respectively. In univariate analysis, the prognostic factors for recurrence were N stage, the number of LN metastases, and extrathyroidal extension. However, multivariate analysis revealed LN metastases and N stage as the only significant prognostic factors after adjusting for confounding factors (P < 0.001). Additionally, multivariate analysis of a subgroup consisting of PTMC patients without N1b revealed the number of central LN metastases as the only significant factor. Therefore, intraoperative examination for central LN metastasis may discriminate high or low risk group.